How vulnerable are care systems to future changes in demand and supply? Providing a framework to compare Austria, Spain, UK and Canada - Ulrike Famira-Mühlberger; Thomas Leoni (Austrian Institute of Economic Research (WIFO), 2024)
This paper examines the evolving landscape of long-term care (LTC) provision in Austria, Spain, UK and Canada, four countries included in the collaborative research project WellCARE. Its aim is to provide a basis to understand the features and vulnerabilities of different care systems, highlighting the mechanisms affecting how and to what extent the demand for care is met today, and identifying the salient issues that will have to be addressed in the future. In the first part, we give an overview of different care regime classifications to provide the analytical framework for comparing and identifying the relevant traits of care systems as well as their trajectories over time. In the second part, we analyse the current care systems in the four countries in greater detail, using recent data covering a broad range of dimensions. Particular attention is paid to analysing how different factors influence the size and composition of the caregiving groups in society. Our analysis reveals the critical role of informal care in all countries, underscored by societal changes such as higher female labour force participation and declining fertility rates. While varying degrees of decommodification characterise LTC systems, all nations grapple with challenges of supply shortages and lengthy waiting lists, particularly in Canada and Spain. Microsimulation modelling is identified as a valuable tool for projecting future LTC demands and assessing policy interventions, accounting for demographic shifts, changing morbidity patterns, and social dynamics.
Keywords: 330